2000
DOI: 10.1021/jf990489j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on the Stability of Plant Phenolic Compounds

Abstract: It is not uncommon to treat plant-derived foods and feeds with alkali. Such exposure to high pH is being used to recover proteins from cereals and legumes, to induce the formation of fiber-forming meat analogue vegetable protein, for preparing peeled fruits and vegetables, and for destroying microorganisms. In addition to their profound effects on functional and nutritional properties in such foods, such treatments may also cause other side reactions, including the destruction of natural polyphenolic compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
419
1
10

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 695 publications
(495 citation statements)
references
References 33 publications
32
419
1
10
Order By: Relevance
“…EGC concentration at pH 8.5 was about 94.7 %. Literature data on the stability of EGC dissolved in buffers at the pH range from 3 to 11 [33] confirm our results showing that EGC is stable at alkaline pH. It additionally supports the conclusion that the observed decrease in the TEAC antioxidant activity of GC comparing to its epimer EGC at pH above 7 is due to poor GC stability at alkaline medium.…”
Section: Resultssupporting
confidence: 89%
“…EGC concentration at pH 8.5 was about 94.7 %. Literature data on the stability of EGC dissolved in buffers at the pH range from 3 to 11 [33] confirm our results showing that EGC is stable at alkaline pH. It additionally supports the conclusion that the observed decrease in the TEAC antioxidant activity of GC comparing to its epimer EGC at pH above 7 is due to poor GC stability at alkaline medium.…”
Section: Resultssupporting
confidence: 89%
“…Recent studies revealed that some types of PCs can be unstable to physiologic pH conditions, suffering irreversible structural changes (Friedman & Jürgens, 2000;Krook & Hagerman, 2012). These studies explain how simple PCs in papaya fruit, like caffeic acid, might be unstable to alkaline conditions above pH 7 (Friedman & Jürgens, 2000). Dn the other hand, a recent study performed by Bouayed et al (2011), reveals similar information about the bioaccessibility of PCs within the food matrix of different apple varieties.…”
Section: Dietary Fiber Content and Associated Phenolic Compoundsmentioning
confidence: 75%
“…Dn the other hand, although there was up to 50% of the total PCs in papaya fruit released at gastric conditions, the intestinal conditions with pancreatin digestion showed a decrease in the PCs concentration, indicating loss of PCs at these conditions. Recent studies revealed that some types of PCs can be unstable to physiologic pH conditions, suffering irreversible structural changes (Friedman & Jürgens, 2000;Krook & Hagerman, 2012). These studies explain how simple PCs in papaya fruit, like caffeic acid, might be unstable to alkaline conditions above pH 7 (Friedman & Jürgens, 2000).…”
Section: Dietary Fiber Content and Associated Phenolic Compoundsmentioning
confidence: 82%
“…The reduction of the content of total flavonoids was 34.16% for the FE samples and 35.12%, for the FEL. t 0 : resting period of 24 h after preparation; values were presented as mean ± standard deviation (n = 3) Flavonoids are phenolic compounds with moderate solubility in water and sensitive to the presence of metal ions, ultraviolet radiation, elevated temperatures and to the hydrolysis, which is accelerated direct and proportionally to an increase of the temperature (Bruneton, 1999;Friedman, Jürgens, 2000). Bilia et al (2001) evaluated the chemical stability of flavonols, a class of flavonoids that rutin is part of, as dry extract added or not with the mixture of ascorbic and citric acid (200:1), as antioxidants, at 2.85%.…”
Section: Resultsmentioning
confidence: 99%